2008
DOI: 10.1038/oby.2008.44
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year Changes in Central Obesity and BMI in Rural and Urban Cameroon

Abstract: Objective: To compare the 10-year changes in the distribution of adiposity in rural and urban Cameroonian populations. Methods and Procedures: Two cross-sectional surveys of populations in the same rural and urban areas of Cameroon, aged ≥24 years, were carried out in 1994 (1,762 subjects) and 2003 (1,398 subjects) using similar methodology. All eligible subjects answered a structured questionnaire on their educational level, alcohol consumption, and tobacco smoking and weight, height, and waist circumference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 14 publications
9
45
1
2
Order By: Relevance
“…The Vietnamese experience suggests that post 1990s, overweight and obese population constantly increased in urban areas, but off late the problem has also started mounting in rural areas (Nguyen et al, 2006;Do et al, 2011). A study conducted in Cameroon during 1994e2003 suggests that overweight and obesity loomed large in urban areas and demonstrated no change during the study period; whereas overweight started rising at very fast in rural areas (Fezeu et al, 2008). An analysis based on eight Indian cities show that nutritional status among women is not significantly associated with lowly developed slum areas or with developed non-slum areas (Gaur et al, 2013).…”
Section: Overweight/obesity and Place Of Residencementioning
confidence: 97%
“…The Vietnamese experience suggests that post 1990s, overweight and obese population constantly increased in urban areas, but off late the problem has also started mounting in rural areas (Nguyen et al, 2006;Do et al, 2011). A study conducted in Cameroon during 1994e2003 suggests that overweight and obesity loomed large in urban areas and demonstrated no change during the study period; whereas overweight started rising at very fast in rural areas (Fezeu et al, 2008). An analysis based on eight Indian cities show that nutritional status among women is not significantly associated with lowly developed slum areas or with developed non-slum areas (Gaur et al, 2013).…”
Section: Overweight/obesity and Place Of Residencementioning
confidence: 97%
“…A WHO report of 2014 indicates that the noncommunicable diseases mentioned above accounted for approximately 31% of total deaths in Cameroon [12]. With respect to the above diseases, earlier reports in Cameroon also indicated that between 1994 and 2003, the age adjusted prevalence of overweight including obesity (BMI ≥25 kg/m 2 ) increased significantly by 54% and 82% for men and women respectively [13,14]. Over the same period, there was a 12.1% and 15.2% increase in age-adjusted prevalence of hypertension among women and men respectively [15], and a 10 fold increase in prevalence of diabetes among adults [16,17].…”
Section: Introductionmentioning
confidence: 94%
“…Sa population est essentiellement cosmopolite, aux us et coutumes très diversifiées notamment en ce qui concerne les habitudes alimentaires. Le processus de transition nutritionnelle y est déjà amorcée (12 Estimation des Paramètres Biochimiques:-Les échantillons de sang sont prélevés à jeun, par ponction veineuse sur héparine. Le plasma obtenu par centrifugation à 3500 tr/mn pendant 10 minutes a servi à l'estimation de la concentration plasmatique du cholestérol total, des triglycérides, du cholestérol HDL, du LDL cholestérol.…”
Section: Matériel Et Méthodes:-unclassified